Cerebrospinal fluid neurofilament light chain levels: marker of progression to generalized amyotrophic lateral sclerosis. (22nd April 2014) - Tortelli, R.; Copetti, M.; Ruggieri, M.; Cortese, R.; Capozzo, R.; Leo, A.; D'Errico, E.; Mastrapasqua, M.; Zoccolella, S.; Pellegrini, F.; Simone, I. L.; Logroscino, G.
<x xml:space="preserve">Abstract</x> Background and purpose To evaluate whether cerebrospinal fluid (CSF) neurofilament light chain (NFL) levels could predict the time to generalization (TTG) in amyotrophic lateral sclerosis (ALS). Methods Cerebrospinal fluid NFL levels of 37 cases of sporadic ALS were measured and the time of symptom spreading from spinal or bulbar localization to both (TTG) was evaluated in all patients. Results Kaplan−Meier analysis showed a short TTG in patients with high NFL levels (log‐rank test chi‐squared = 19.4, P < 0.0001). In a multivariate regression model patients with NFL levels above the median had an eight‐fold higher risk of generalization (adjusted hazard ratio 7.9, 95% confidence interval 2.9–21.4, P < 0.0001) compared with those with NFL levels below the median. Conclusions This study shows that in sporadic ALS NFL, a marker of neurodegeneration, is correlated with TTG, a clinical intermediate parameter of survivorship.